IGTAI - an Idea Generation Tool for Ambient Inteligence - Freitas, Carlos Filipe (2013)
Today, business group decision making is an extremely important activity. A considerable number of applications and research have been made in the past years in order to increase the effectiveness of decision making process. In order to support the idea generation process, IGTAI (Idea Generation Tool for Ambient Intelligence) prototype was created. IGTAI is a Group Decision Support System designed to support any kind of meetings namely distributed, asynchronous or face to face. It aims at helping geographically distributed (or not) people and organizations in the idea generation task, by making use of pervasive hardware in a meeting room, expanding the meeting beyond the room walls by allowing a ubiquitous access through different kinds of equipment. This paper focus on the research made to build IGTAI prototype, its architecture and its main functionalities, namely the support given in the different phases of the idea generation meeting.